Jin's Three Needle Acupuncture and Moxibustion Reduce Pain Intensity in Gastritis - Eka Diah Amiroh; Sholichan Badri; Nurmila Mutiah (Poltekkes Kemenkes Surakarta, 2023)
Background: Gastritis is a common disease in the community caused by unhealthy lifestyles. Long-term repeated use of stomach medication has the potential to cause side effects and organ damage. Acupuncture is an effective therapy for chronic pain that has long-lasting effects without side effects. This study aims to determine the effect of Jin's Three Needle acupuncture and moxibustion therapy on pain intensity in gastritis patients. Methods: This study used a true experimental design with a two-group pretest-posttest design. The sample consisted of 30 respondents who met the inclusion and exclusion criteria, divided into two groups. Group 1 received Jin's Three Needle acupuncture and moxibustion therapy, while group 2 received only Jin's Three Needle acupuncture therapy. The measurement instrument used a pain scale. Data analysis used the Shapiro-Wilk normality test, followed by an independent t-test and Mann-Whitney test. Results: The analysis showed that the group receiving Jin's Three Needle acupuncture and moxibustion therapy experienced a more significant reduction in pain scale compared to the acupuncture-only therapy group with a p-value of <0.001. Conclusion: Jin's Three Needle acupuncture therapy combined with moxibustion is effective in reducing the intensity of gastritis pain. The combination of acupuncture and moxibustion therapy is recommended as an alternative treatment for gastritis to increase effectiveness and reduce the side effects of gastric medication.